The Effect of Dietary Modification and Nutritional Education on Nutrition Care Process (NCP) for Increasing Dietary Intake, Body Weight, and Nutritional Status of Cancer Patients at Risk of Malnutrition and Malnourished in the Inpatient of Dharmais Cancer - Fauzatun Hadiyati; Ratna Supriastuti; Arifah Mujiharti (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: Cancer patients that are hospitalized often have problems with their nutrient intake. Low nutrient intake can be affected by malnutrition. In cancer patients, the intake of nutrients needs to be considered specifically in relation to the occurrence of metabolic changes that lead to decreased nutritional status. The objective of this study is to analyze the effect of dietary modification and nutritional education on nutrition care process (NCP) for increasing dietary intake, body weight, and nutritional status of malnourished cancer patients and cancer patients at risk of malnutrition.Methods: The study was a quasi-experiment with one-group pretest-posttest design. The population consisted of all new adult hospitalized cancer patients. The data were collected from July to September 2019. The statistical analysis used paired sample t-test. Dietary modification and nutritional education were given individually based on each nutrition problem of the patient and their nutritional needs.Results: There were 83 patients involved for the study. Most of the patients were female (61.4%), aged over 45 years (62.7%), graduated from high school (47%), were housewives (49.4%), and had clinical histories of no comorbidities (90.4%). Most of them had improvement in general condition (74.7%). The study showed significantly increasing dietary intake of energy (889.7 calorie), protein (36.4 gr), fat (49.3 gr), and carbohydrate (131.4 gr) (p = 0.000). The increasing percentage of nutrient intake to nutritional needs before and after intervention of NCP was 39.8 to 88.6% for energy, 44.4 to 104% for protein, 51 to 120% for fat, and 41.5 to 90.1% for carbohydrate. The average increase (but not significant related correlation) in body weight was 0.16 kg (p = 0.141) and body mass index 0.05 kg/m2 (p = 1.94). Conclusions: Dietary modification and nutritional education on NCP improve dietary intakes (energy, protein, fat, and carbohydrate) of cancer patients at risk of malnutrition and being malnourished.